Diagnóstico clínico y de laboratorio en pacientes con cáncer de hígado. - Salán Barrera, Sayanara Teresa (2025)
Liver cancer is a malignant disease that affects liver function and presents high incidence and mortality rates worldwide. Although it is more prevalent in men, an increase in the frequency of cases among women has been observed in recent years. This research was based on a bibliographic review aimed at gathering scientific information on the clinical characteristics and biomarkers used in the diagnosis of liver cancer. It is a descriptive, documentary, and non-experimental study with a retrospective approach. A total of 41 articles were selected based on inclusion and exclusion criteria, from an initial pool of 88 reviewed scientific papers. The analyzed information was obtained from well-known sources such as ScienceDirect, PubMed, Medigraphic, SciELO, and Redalyc, among other specialized databases. The review determined that the average age at diagnosis is approximately 57 ± 12 years in men and 61 ± 4 years in women. The main predisposing condition identified was liver cirrhosis, which is closely associated with chronic infections caused by hepatitis B and C viruses. Regarding disease detection, the most commonly used tumor biomarkers include alpha-fetoprotein (AFP),carbohydrate antigen 19-9 (CA 19-9), and carcinoembryonic antigen (CEA). These markers allow for a more accurate evaluation of the histological type of liver cancer, facilitating its classification and diagnosis.